Evaluation of preadolescent athletes` running performance in a middle distance event - Pilianidis, T.; Mantzouranis, N.; Siachos, N.; Smirniotou, A.; Zacharogiannis, I.; Kellis, S. (Trends in Sport Sciences, 2013)
Introduction. Sport biomechanics focuses on the evaluation of athletes` running stride characteristics with training shoes and barefoot. Few studies have assessed the running performance of shod and unshod preadolescent athletes, and they have been carried out only in laboratory conditions. Aim of Study: The aim of this study was to evaluate the performance of preadolescent athletes in the 1000 m running event by applying two protocols: with training shoes and barefoot. Material and Methods. Forty three (n = 43) preadolescent athletes were recruited for the study. In the first testing session the participants` anthropometric data and their VO2max were recorded. The athletes were randomly assigned to compete in two testing protocols in counterbalanced order. The t-test assessed the performance in two protocols while the ROC curves were applied to illustrate the discrimination between performances relative to the athletes` gender. Pearson`s correlation coefficient analysis was applied to evaluate the intercorrelations between the athletes` VO2max, and their anthropometric characteristics during an 1000m running event shod and unshod. Results. The results showed that boys performed better than girls in the 1000 m event, shod and unshod. Pearson`s correlation analysis presented a substantial effect on the VO2max and body fat in the preadolescents` performance in both protocols. In spite of the fact that boys performed slightly better than girls, the t-test did not confirm the significant differences in the athletes` 1000 m performance barefoot. Conclusions. The importance of the present study lies in the fact that the running performance of preadolescent athletes barefoot is not worse than their performance in training shoes, and this can provide an incentive for future research concerning the content of training programs of young athletes.